Thursday

December 18, 2014

December 18, 2014

Posted by **Anonymous** on Saturday, October 29, 2011 at 11:10pm.

- calculus -
**Steve**, Monday, October 31, 2011 at 5:05amI think it should help to notice that

5n^2 + 6n + 3 = 3n^2 + 6n + 3 + 2n^2 = 3(n+1)^2 + 2n^2

So, what you have is just

3/n^2 + 2/(n+1)^2

**Answer this Question**

**Related Questions**

statistics - I'm trying to work through the proof for SST = SSM + SSE MEAN = &#...

Calculus - Suppose that f(x), f'(x), and f''(x) are continuous for all real ...

calculus - Find the value of the constant C that makes the following function ...

Math - ∑(x+y) c. ∑(x+∑(y)) d. ∑x+ ∑y e. ∑(x...

math pre calculus - Let A=(-2,INF] and B=(2,INF). FIND: a.)AUB b.)A (UPSIDE ...

Calculus (Please Check) - Show that the equation x^5+x+1 = 0 has exactly one ...

Calculus - Find a series ∑a_n for which ∑(a_n)^2 converges but &#...

Math - Mathematical Induction - 3. Prove by induction that∑_(r=1)^n▒...

Calculus - This integral does not converge using the normal (Leibniz) ...

CALCULUS - 6. f(x)= 12x^5 + 30x^4 - 160x^3 +4 For this function there are four ...